2013
DOI: 10.1074/jbc.m112.437749
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-182 and MicroRNA-200a Control G-protein Subunit α-13 (GNA13) Expression and Cell Invasion Synergistically in Prostate Cancer Cells

Abstract: Background: G-protein-coupled receptor (GPCR) signaling through the GNA12/13-Rho axis has been linked to cancer cell invasion and metastasis. Results: MicroRNAs regulate GNA13 expression and cancer cell invasion. Conclusion: Loss of miR-182 and miR-200a in prostate cancer cells induces GNA13 expression and SDF-1-mediated invasion. Significance: Suppressing GNA13 expression using microRNAs could inhibit GPCR-mediated cancer cell invasion and metastasis in prostate cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 38 publications
6
82
0
Order By: Relevance
“…In this study, miR-200a was over-expressed by 3.65 folds in cervical carcinoma compared to normal tissues respectively. Similar studies indicated the miR-200a was up regulated which may supporting the concept that miR-200a functions as oncogene (Cong et al, 2013;Rasheed et al, 2013;Yu et al, 2013). In our study, the over-expression of miR-200a was associated with the over-expression of MMP2, MMP9.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, miR-200a was over-expressed by 3.65 folds in cervical carcinoma compared to normal tissues respectively. Similar studies indicated the miR-200a was up regulated which may supporting the concept that miR-200a functions as oncogene (Cong et al, 2013;Rasheed et al, 2013;Yu et al, 2013). In our study, the over-expression of miR-200a was associated with the over-expression of MMP2, MMP9.…”
Section: Discussionsupporting
confidence: 73%
“…This discovery simultaneously identified BRD3, UBAP1 and PTEN as direct targets of miR-141. MiR-141 showed an inverse correlation to the protein expression of G-protein subunit a-13 in prostate cancer cells, and forced overexpression of miR-141 negatively regulated the invasion capability of prostate cancer cells [59]. Interestingly, Xiao et al have found that Small heterodimer partner was a target of miR-141 and was downregulated in cultured human PCa cells with the involvement of upregulation of miR-141, which accelerated AR transcriptional activity [60].…”
Section: Upstream and Downstream Pathways Of Mir-141mentioning
confidence: 99%
“…Little is known about the specific functions of G␣ 13 in cancer, and those studies have focused on G␣ 12 (29). It is documented that G␣ 13 expression is markedly increased during prostate cancer progression and that micro RNAs regulate its expression post-transcriptionally (62). G␣ 13 also mediates lysophosphatidic acid-stimulated invasive migration of pancreatic cancer cells (63).…”
Section: Discussionmentioning
confidence: 99%